Representaciones culturales de América Latina y Caribe un análisis de La música en Cuba de Alejo Carpentier - Pontes, Renata (2016)
This analysis of Alejo Carpentier’s historiography La música en Cuba (1946) addresses the inclusion of afrocubanismo in the composition of Cuban music and culture in connection with the debates on nationalism and vanguardism. Carpentier’s vision of time and the concept of magical realism, related to the “authenticity” of Latin America, abound throughout Carpentier’s literature, and this book is no exception. Meanwhile, his position on the labor of the Latin American writer gains special emphasis as music becomes the principal element in the shaping of nationality. This work, which proposes that music is the key to the “originality” of Cuban culture, also analyzes the role played by intellectuals in an era in which literature “assumed a central position within the component forces of the country’s or region’s culture” (Angel Rama, 1985).